129k views
2 votes
- 6(x + 2) + 2x - 4 = 8(x - 2) + 8
does this have a solution if do why

2 Answers

3 votes

Answer: Yes, there is a solution: - 2/3

Step-by-step explanation: Step 1:

- 6 ( x + 2 ) + 2x - 4 = 8 ( x - 2 ) + 8

Step 2:

- 6x - 12 + 2x - 4 = 8x - 16 + 8

Step 3:

- 4x - 16 = 8x - 8

Step 4:

- 16 = 12x - 8

Step 5:

- 8 = 12x

Step 6:

- 8/12 = - 2/3

Answer:

- 2/3

User Hossein Salmanian
by
5.4k points
5 votes

Answer:

Yes, there is a solution: - 2/3

Explanation:

Step 1:

- 6 ( x + 2 ) + 2x - 4 = 8 ( x - 2 ) + 8

Step 2:

- 6x - 12 + 2x - 4 = 8x - 16 + 8

Step 3:

- 4x - 16 = 8x - 8

Step 4:

- 16 = 12x - 8

Step 5:

- 8 = 12x

Step 6:

- 8/12 = - 2/3

Answer:

- 2/3

Hope This Helps :)

User Pspl
by
5.4k points